Old and new specimens of a poorly known glyptodont from the Miocene of Patagonia and their biochronological implications - Gonzalez Ruiz, Laureano Raul (2016)
The Palaehoplophorini is a tribe of glyptodonts represented by fragmentary specimens for which the oldest records occur in the Pedregoso and Río Mayo formations (middle-late Miocene) in Patagonia (Argentina). The mammal fossils from those formations were the basis for the recognition of the Mayoan fauna, placed between the Friasian sensu stricto/Colloncuran-Laventan and the Chasicoan faunas. The only identified glyptodont from Río Mayo Formation is Palaehoplophorus meridionalis represented only by its type material (i.e., caudal tube) and the precise provenance is unknown. We describe a new specimen of Palaehoplophorus meridionalis collected in the Río Mayo Formation represented by associated osteoderms of the dorsal carapace and postcranial elements, plus part of the type and assigned specimens that remain unpublished from the old collection. This is the first description of osteoderms from the dorsal carapace of this species and postcranial elements (the first for a Palaehoplophorini), and the first glyptodont with precise provenance from Río Mayo Formation. As result of improving the description and emending the diagnosis, we agree with previous authors about the basal position of Palaehoplophorus meridionalis within the tribe. Finally, we review the Glyptodontidae association of the Mayoan fauna, which are exclusively represented by Palaehoplophorini (Palaehoplophorus meridionalis and Palaehoplophoroides rothi) and Glyptodontidae indet. This association supports a greater affinity of this fauna with the younger Chasicoan than with the older Friasian sensu stricto/Colloncuran-Laventan faunas.